2020
DOI: 10.5194/aab-63-277-2020
|View full text |Cite
|
Sign up to set email alerts
|

Drip loss assessment by EZ and bag methods and their relationship with pH value and color in mutton

Abstract: Abstract. Drip loss, pH value, and color are among the important traits that determine meat quality. Contrary to pH and color, the method associated with drip loss is not yet standardized, and literature data are difficult to compare. Besides, to our knowledge, there is no research comparing drip loss methods and their relation with pH and color in mutton. This study aimed to assess drip loss measurements in mutton taken by different methods (EZ and bag – BM) and their relationship with pH values and color. Mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 14 publications
1
5
2
Order By: Relevance
“…As already mentioned, an increase in drip loss over time is expected, as exudation is known to be a slow process that lasts for days, during which water expelled from the myofibrils accumulates in the muscle [ 14 ]. The results of the present study ( Table 1 and Table 2 ) are in accordance with previous studies using the EZ-DripLoss method [ 2 , 11 , 15 , 16 , 17 ].…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…As already mentioned, an increase in drip loss over time is expected, as exudation is known to be a slow process that lasts for days, during which water expelled from the myofibrils accumulates in the muscle [ 14 ]. The results of the present study ( Table 1 and Table 2 ) are in accordance with previous studies using the EZ-DripLoss method [ 2 , 11 , 15 , 16 , 17 ].…”
Section: Resultssupporting
confidence: 92%
“…With chicken breast meat, Graberec et al [ 16 ] also reported lower average drip losses within 24 h (2.38%) than within 48 h (2.74%). In a study on pork meat, Filho et al [ 2 ] found average drip losses of 3.13% within 24 h and 5.19% within 48 h. With mutton, Kaić et al [ 17 ] reported average drip losses of 0.65% within 24 h and 0.93% within 48 h. With lamb meat, Holman et al [ 11 ] also reported that drip losses increased with the measurement interval (0.41% = 24 h; 0.67% = 48 h; 0.96% = 72 h; and 1.49% = 96 h).…”
Section: Resultsmentioning
confidence: 99%
“…On the contrary, lower average drip loss values of weighed samples were found with lamb [ 13 ], mutton [ 14 ], and meat from adult horses [ 16 ] than the ones of the present report. Namely, Kaić et al [ 14 ] aimed to assess drip loss measurements in mutton that were taken by EZ-DripLoss and bag methods, and reported average drip losses of 0.65% within 24 h and 0.93% within 48 h. Holman et al [ 13 ] investigated the effect of muscle fiber orientation and measurement interval on lamb meat drip losses using the EZ-DripLoss method, and found average drip losses of 0.41% within 24 h, 0.67% within 48 h, 0.96% within 72 h, and 1.49% within 96 h. Razmaitė et al [ 16 ] aimed to assess the influence of gender, age, and carcass weight on the properties of meat from adult obsolescent horses.…”
Section: Resultscontrasting
confidence: 96%
“…On the contrary, lower average drip loss values of weighed samples were found with lamb [ 13 ], mutton [ 14 ], and meat from adult horses [ 16 ] than the ones of the present report. Namely, Kaić et al [ 14 ] aimed to assess drip loss measurements in mutton that were taken by EZ-DripLoss and bag methods, and reported average drip losses of 0.65% within 24 h and 0.93% within 48 h. Holman et al [ 13 ] investigated the effect of muscle fiber orientation and measurement interval on lamb meat drip losses using the EZ-DripLoss method, and found average drip losses of 0.41% within 24 h, 0.67% within 48 h, 0.96% within 72 h, and 1.49% within 96 h. Razmaitė et al [ 16 ] aimed to assess the influence of gender, age, and carcass weight on the properties of meat from adult obsolescent horses. They found that the average drip losses for mares was 1.22%, for stallions was 0.77%, and for geldings was 0.43% within 24 h Compared to our results, lower drip loss values of weighed samples that were found in mutton, lamb, and horse meat could be related to the numerous properties that affect WHC and depend on many interrelated factors, so it is difficult to explain when considering each of them independently.…”
Section: Resultscontrasting
confidence: 96%
See 1 more Smart Citation